2018
DOI: 10.1080/15563650.2018.1433299
|View full text |Cite
|
Sign up to set email alerts
|

Bromoxynil and 2-methyl-4-chlorophenoxyacetic acid (MCPA) poisoning could be a bad combination

Abstract: We would like to provide further research findings following the case reports on "2-methyl-4chlorophenoxyacetic acid (MCPA) and bromoxynil herbicide ingestion" by Chiew et al. [1]. This reported a characteristic toxicity profile of hyperthermia, hypercapnia and metabolic acidosis in two patients that responded to aggressive active cooling and supportive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The clinical effects and laboratory features have been reported in fine detail in only a few small case series 1 , 2 . A much larger prospective cohort study reported 8 deaths in 181 cases from Sri Lanka with some limited clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical effects and laboratory features have been reported in fine detail in only a few small case series 1 , 2 . A much larger prospective cohort study reported 8 deaths in 181 cases from Sri Lanka with some limited clinical data.…”
Section: Introductionmentioning
confidence: 99%